2018
DOI: 10.3390/toxins10060243
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mycotoxin Residues on Ready-to-Eat Food by Chromatographic Methods Coupled to Mass Spectrometry in Tandem

Abstract: Simultaneous determination of twenty-seven mycotoxins in ready-to-eat food samples using “Quick Easy Cheap Rough and Safe” (QuEChERS) extraction and chromatographic methods coupled to mass spectrometry in tandem is described in this study. Mycotoxins included in this survey were aflatoxins (B1, B2, G1, G2), enniatins (A, A1, B, B1), beauvericin (BEA), fumonisins (FB1, FB2), sterigmatocystin (STG), deoxynivalenol (DON), 3-acetyl-deoxynivalenol (3-ADON), 15-acetyl-deoxynivalenol (15-ADON), nivalenol (NIV), neoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Because this fungi often contaminate food, feedstock, and animal feed, BEA is a risk factor for environmental health. Although the cereal-based food and feed contamination of Fusaria is huge, and although BEA is regularly found in these products (Hietaniemi et al, 2016 ; Svingen et al, 2017 ; Beccari et al, 2018 ; Carballo et al, 2018 ), the EFSA Panel on Contaminants in the Food Chain (CONTAM Panel, 2014 ) concluded that acute exposure to BEA and ENNs do not indicate concern for human health.…”
Section: Risk Assessment Of Beauvericin In Food and Feedmentioning
confidence: 99%
“…Because this fungi often contaminate food, feedstock, and animal feed, BEA is a risk factor for environmental health. Although the cereal-based food and feed contamination of Fusaria is huge, and although BEA is regularly found in these products (Hietaniemi et al, 2016 ; Svingen et al, 2017 ; Beccari et al, 2018 ; Carballo et al, 2018 ), the EFSA Panel on Contaminants in the Food Chain (CONTAM Panel, 2014 ) concluded that acute exposure to BEA and ENNs do not indicate concern for human health.…”
Section: Risk Assessment Of Beauvericin In Food and Feedmentioning
confidence: 99%
“…Fluorescence detectors are restricted for the individual quantification of FB1 [38,46,47], the sum of FB1, FB2, FB3 [41] or the separate determination of up to three group B fumonisins [42,55]. On the other hand, one of the main advantages of mass spectrometry detectors is the possibility of performing multiplex analysis, not only for different mycotoxins [48,49,50,53,54,57,58,59,60,61,64,65,66,67,71,72,73,74,77,79,80,187], but also when combined with varied metabolites. Growth regulators, antibiotics, pesticides [51,70,75], and other fungal metabolites [63,68], were simultaneously identified in analysis capable of assessing up to 74 and 90 compounds [62,78].…”
Section: Chromatographic Detection Of Fumonisin B1mentioning
confidence: 99%
“…Yet, the use of specific IS and a validated method for a single matrix, could reduce the scope of the determination, and increase its final cost. Notwithstanding, some approaches proposed the application of the aforementioned procedures combined with clean up techniques and QuEChERS, for a greater method validation [58,69,71,73].…”
Section: Chromatographic Detection Of Fumonisin B1mentioning
confidence: 99%
“…Aflatoxin B1 (AFB1), the most toxic and prevalent [ 2 ], is a potent human carcinogen [ 6 ]. Aflatoxins are moderately stable under normal cooking and industrial processing procedures [ 4 , 7 , 8 ]. There have been reports of acute human and animal aflatoxicosis outbreaks resulting in deaths [ 9 , 10 ] and widespread exposure to chronic dietary aflatoxins [ 2 , 11 ].…”
Section: Introductionmentioning
confidence: 99%